Hazardous material management and hazard communication - Haight, Joel M. (American Society of Safety Engineers, 2012)
This volume examines the regulatory information and best practices to manage hazardous materials and communicate hazards to their employees and first responders. The editor introduces OSHA's Hazard Communication Standard (HCS) requirements, mandating that employers disclose information about toxic and hazardous substances used in workplaces. Benchmarking, performance criteria and best practices are examined in detail concerning the HCS is examined. The editor provides detail on the standard's provisions and application, including the use of Safety Data Sheets (SDSs). The text also examines the EPA and DOT also regulations regarding hazardous spills and releases.